A case report of management of cardiomyopathy in a patient with prior COVID infection - Meghan I Cook; Alix Zuleta-Alarcon; Kasey Fiorini; Yun Xia; David L Stahl (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
The novel coronavirus (SARS-CoV-2) is responsible for the current pandemic and while most patients have mild symptoms, severe COVID-19 infections can have long-lasting symptoms. There is data to suggest that sequelae from COVID-19 persist for months. Viral myocarditis and cardiomyopathy related to COVID-19 have been described in the non-pregnant population. We present a case of a parturient presenting with left ventricular global hypokinesis and ejection fraction of 38% two months after initial COVID-19 infection. Pregnant patients with COVID-19related cardiomyopathy should be managed by a multidisciplinary team. We suggest considering SARS-CoV-2 infection in parturients presenting with symptoms of decompensated heart failure.